PENGARUH MEDIA LOCKER BILANGAN TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 4-5 TAHUN DI TK ISLAM AKRAMUNNAS PEKANBARU - ', Nurweti; ', Zulkifli N; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of observations in the field can be seen that the ability to recognize the concept of the number of children aged 4-5 years has not developed optimally. So that should be the application of media locker numberr. This study aims to determine the effect of the application of media locker numbers toward the ability to know the concept of numbers. This research was conducted in Islamic Kindergarten Akramunnas Pekanbaru. The research used experimental method with one group pre-test post-test design with 20 samples of children. The data collection techniques were used that observation. Technique Data analysis using t-test test by using program SPSS 17.0. Result of data analysis obtained tcount = 23,126 bigger than ttable = 2,093 with sig.0,00 <0,05. It can be concluded that there are differences in the ability to know the concept of numbers before and after the using media locker numbers. Influence given by media locker number based on formula N Gain equal to 69,61%.Keywords:Concepts of Numbers, Locker Numbers.